Tata Kelola Kota Layak Anak: Sebuah Analisis Bibliometrik - Nila Wahyuni (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
This study aims to analyze the scientific literature on child-friendly city governance using the Bibliometric Analysis framework. Analysis using VOSviewer software version 1.6.19 with database from Google Scholar. The search for articles uses Publish or Perish software version 8, assisted by the Mendeley Desktop software version 1.19.8 in completing the article data. The keywords used in the search were "governance" and "child-friendly cities." By using these keywords, 307 article documents obtain. The articles were sorted and eliminated in two stages, resulting in 29 documents. Furthermore, literature analysis carries out in four parts: publication analysis, institutional contribution analysis, citation analysis, and keyword analysis. In general, the results show that in recent years there has been an increase in the scientific literature on the theme of child-friendly urban governance. However, these articles and annual citations still need to be higher. In addition, published articles can group into five clusters of research themes.